Study on Seroprevalence of Contagious Caprine Pleuropneumonia in Goats Marketed in Kathmandu Valley - Rai, Anisha; Sharma, Barun Kumar (Nepalese Journal of Agricultural Sciences, 2026)
Contagious caprine pleuropneumonia (CCPP) is a highly contagious respiratory disease of small ruminants that is caused by gram-negative, pleomorphic, facultative anaerobic bacterium Mycoplasma capricolum, sub-sp. Capripneumoniae. It is a severe respiratory disease of goats characterized by high morbidity and mortality, as well as the potential to spread across borders. A study was conducted to determine the seroprevalence of CCPP in the marketed goats of Kathmandu Valley of Nepal from June to August, 2024. The study was conducted in goats entering the Kathmandu valley through a Quarantine check post of Nagdhunga, Kathmandu to assess the prevalence of CCPP. A total of 168 goat serum samples were tested using a competitive enzyme-linked immunosorbent assay (c-ELISA) (IDEXX CCPP Ab test kit, United States) for antibodies against Mycoplasma capricolum capripneumoniae. Out of the total serum samples tested, 15 (8.9%) samples were seropositive for CCPP. Significantly higher seroprevalence was observed among goats of Rukum-Paschim 3 (50%), and Kailali 2 (22.2%) followed by Baitadi 1 (14.3%), Bardiya 3 (14.3%), Parasi 1 (14.3%), Kanchanpur 2 (12.5%), Rolpa 1 (7.7%), Dang 1 (2.4%) and Kathmandu 1 (2.8%). The result was negative in Salyan and Makwanpur districts. This study revealed the presence of CCPP in the goat population of Nepal and the potential circulation of the pathogen inside the country. Therefore, appropriate preventive measures such as maintaining effective biosecurity, minimizing stress in goats, and conducting regular research and investigations should be implemented to prevent potential disease outbreaks.